The impact of high temperatures on performance in work-related activities - Matteo Picchio; Jan C. van Ours (Global Labor Organization (GLO), 2023)
High temperatures can have a negative effect on work-related activities because workers may experience difficulties concentrating or have to reduce effort in order to cope with heat. We investigate how temperature affects performance of professional tennis players in outdoor singles matches in big tournaments. We find that performance significantly decreases with ambient temperature. This result is robust to including wind speed and air pollution in the analysis. There are no differences between men and women. However, there is some heterogeneity in the magnitude of the temperature effect in other dimensions. In particular, we find that the temperature effect is smaller when there is more at stake. Our findings also suggest that the negative temperature effect is smaller if the heat lasts, i.e. there is some adaptation to high temperatures.
Keywords: J24; J81; Q51; Q54; 330; Climate change; temperatures; tennis; performance; productivity